The Influence Of Emotional Branding To Customer Loyalty: A Qualitative Assessment - Fresiana, Anisa Dinda; Iskandar, Budi Permadi (Journal of Business and Management, 2020)
Abstract. Businesses or brands collaborate with their customers to fulfill their desires and aspirations. Followed by 2019 government records, there are new cosmetics industries in Indonesia, raising the figure from 760 in 2018 to 797 industries. It means, cosmetic industry competition will be more intense in the future. The objective of this research is to assess if there is a relationship between the four elements of emotional branding to consumer loyalty of the brand Make Over. A qualitative grounded theory is used for this research through a semi-structured in-depth interview. The findings are relationship, sensorial experience, and imagination have a relation to customer loyalty. After theobserving with Gobe's theory, the results can be used for formation of consumer loyalty. This research will contribute to both practitioners and academics. For the practitioners, it should provide understanding, insight, and benefits; especially for brands or businesses in the cosmetics industry. For academics, it can fill the literature gap by developing theories to the formation of customer loyalty through the elements of emotional branding that have been assessed.Keywords: Emotional Branding, Customer Loyalty, Make Over, Qualitative Approach